Detection of naringenin and kaempferol in justicia gendarussa leaf extracts by GC-FID - Zahidah Ayob,; Shajarahtunnur Jamil,; Siti Pauliena Mohd Bohari,; Farediah Ahmad,; Azman Abd Samad, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Justicia gendarussa methanolic leaves extract from four different locations in Southern region of Malaysia and distribution of two flavonoids, naringenin and kaempferol in plant organs (young and mature leaves) were determined using gas chromatography-flame ionization detector (GC-FID) analysis. Naringenin and kaempferol contents were detected and quantified in leaves extract. The results indicated that mature leaves contained more naringenin and kaempferol compared to young leaves. The highest concentration of naringenin and kaempferol were recorded in mature leaves from Skudai and Muar regions which were 507.692 and 1226.964 mgkg-1, respectively. Data analysis showed that naringenin content was directly proportional to the amount of kaempferol in the leaf extracts. In conclusion, this study suggested geographical variation among plant samples and physiological stage of organ parts could contribute to variation in flavonoids concentration in a plant species.